2018
DOI: 10.1097/gox.0000000000001688
|View full text |Cite
|
Sign up to set email alerts
|

Management of Airway Obstruction in Infants With Pierre Robin Sequence

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Since the publication of a seminal paper by Sher in 1992, it has been understood that although micrognathia-associated glossoptosis underlies the airway obstruction in all patients with PRS to some extent, clinical airway obstruction is determined by a number of causes, including neurologic dysfunction, rate of neuromuscular maturation, and laryngomalacia (Randall et al, 1965; Sher, 1992; Morice et al, 2018). Additionally, Runyan et al (2018) published a retrospective analysis of 171 patients with PRS and found that the most significant factor predictive of surgical intervention was a high obstructive index on preintervention sleep study; the authors noted no differences in micrognathia between patients managed conservatively and those managed surgically ( P = 1.000) (Runyan et al, 2018). Morice et al (2018) have also reported that grades of retrognathia and glossoptosis are not predictive of respiratory and feeding disorder severity in both patients with syndromic and nonsyndromic PRS (Morice et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of a seminal paper by Sher in 1992, it has been understood that although micrognathia-associated glossoptosis underlies the airway obstruction in all patients with PRS to some extent, clinical airway obstruction is determined by a number of causes, including neurologic dysfunction, rate of neuromuscular maturation, and laryngomalacia (Randall et al, 1965; Sher, 1992; Morice et al, 2018). Additionally, Runyan et al (2018) published a retrospective analysis of 171 patients with PRS and found that the most significant factor predictive of surgical intervention was a high obstructive index on preintervention sleep study; the authors noted no differences in micrognathia between patients managed conservatively and those managed surgically ( P = 1.000) (Runyan et al, 2018). Morice et al (2018) have also reported that grades of retrognathia and glossoptosis are not predictive of respiratory and feeding disorder severity in both patients with syndromic and nonsyndromic PRS (Morice et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…More recently published studies about RS tend not to require CP for inclusion, likely reflecting expert consensus guidelines emphasizing this point (Breugem et al, 2016). In cohorts ascertained according to the 2016 consensus criteria, prevalence of CP ranges from 43% to 92% (Basart et al, 2015; Daniel et al, 2013; Flores et al, 2015; Runyan et al, 2018). Although intact palate was identified in one study as a risk factor for unsuccessful treatment with mandibular distraction osteoegenesis, there has overall been minimal investigation into whether there are differences in outcomes or etiologies between children with RS based on presence of absence of CP (Flores et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Higher prevalence of CP is observed in RS cohorts ascertained without requiring uniform, objective evaluation for airway obstruction such as polysomnography (Daniel et al, 2013; Flores et al, 2015; Holder‐Espinasse et al, 2001; Kam et al, 2015; Runyan et al, 2018; Thouvenin et al, 2013). We speculate that the presence of CP in a micrognathic child represents an obvious reminder to clinicians to consider the possibility of RS.…”
Section: Introductionmentioning
confidence: 99%
“…Infants treated by conservative technique and with MDO had developed long‐term feeding and airway obstruction results in comparison with the tracheostomy group. 20 …”
Section: Discussionmentioning
confidence: 99%